2022
DOI: 10.21149/13119
|View full text |Cite
|
Sign up to set email alerts
|

Supervivencia y factores asociados en pacientes con cáncer cervicouterino atendidas por el Seguro Popular en México

Abstract: Objetivo. Estimar la supervivencia a cinco años por cáncer cervicouterino y sus factores asociados en pacientes mexica­nas, cuya atención fue financiada por el Fondo de Protección contra Gastos Catastróficos (FPGC) del Seguro Popular durante el periodo 2006-2014. Material y métodos. Se analizó la base de datos de las pacientes mencionadas y se vinculó con el Subsistema Epidemiológico y Estadístico de Defunciones. Se hizo un análisis de supervivencia a cinco años por etapa clínica y factores asociados, mediante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Overall survival (OS) at 5 years was 68.5%. The OS analysis by clinical stage was 88% in early stages, 63.9% in locally advanced disease, and 43.6% for advanced disease ( 8 ). The results of this study found 5-year survival rates comparable to the reported for other countries, which are 63%, 66%, 67%, and 58.8% for Spain, the USA, Chile, and Colombia, respectively.…”
Section: Tertiary Prevention In Mexico (Treatment)mentioning
confidence: 97%
See 3 more Smart Citations
“…Overall survival (OS) at 5 years was 68.5%. The OS analysis by clinical stage was 88% in early stages, 63.9% in locally advanced disease, and 43.6% for advanced disease ( 8 ). The results of this study found 5-year survival rates comparable to the reported for other countries, which are 63%, 66%, 67%, and 58.8% for Spain, the USA, Chile, and Colombia, respectively.…”
Section: Tertiary Prevention In Mexico (Treatment)mentioning
confidence: 97%
“…Recently, in 2022, a retrospective analysis was published that included more than 20,000 patients diagnosed with CC, whose treatment was financed by the Popular Insurance Catastrophic Expenditure Protection Fund (FPCGC). The prevailing clinical stage at the time of diagnosis was locally advanced disease (FIGO) in 14,782 women (68.5%), followed by early disease in 5,286 patients (24.5%) and advanced disease in 1488 women, corresponding to 6.9% ( 8 ). Among 346 CC patients treated at an oncology hospital, more than half of the women did not have a formal job (57%), two-thirds of the women had social security through a family member or their retirement, and 32% had social security coverage through their employment.…”
Section: Cervical Cancer In Mexicomentioning
confidence: 99%
See 2 more Smart Citations
“…In developing countries, such as Mexico, a high proportion of CC cases are diagnosed in advanced clinical stages, resulting in lower survival and a high mortality rate [ 8 ], which is largely due to the lack of effective cervical cancer screening programs. In Mexico, more than 70% of cervical cancer patients are detected in locally advanced or advanced stages [ 9 ], while the overall survival (OS) worsens as the clinical stage progresses [ 10 ]. Disease characteristics related to clinical stages, such as tumor size, lymph node infiltration, and distant metastasis, are related to patient survival; however, not all patients with the same clinical stage have the same outcome.…”
Section: Introductionmentioning
confidence: 99%